Splintering urbanism : networked infrastructures, technological mobilities and the urban condition - Graham, Stephen, 1965- (Routledge, 2001)
This text offers an international and interdisciplinary analysis of the complex interactions between infrastructure networks and urban spaces. Drawing on case studies and examples from across the globe, it offers a statement on the urban condition.